2015
DOI: 10.1590/1516-1439.315014
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Mechanical Properties of Radiofrequency Ar-N2 Plasma Nitrided Aluminium

Abstract: Aluminium (Al) samples were nitrided in 13.56 MHz radiofrequency (RF) discharge of 70:30 vol.% Ar:N 2 mixture at substrate temperature of 400 °C and RF power of 300 W for different fill pressures and treatment times. The nitrided samples were then characterized for their structural and mechanical properties using x-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive x-ray spectroscopy (EDS), and Vickers micro hardness testing. XRD peaks (110), (111) and (200) of aluminium nitride (AlN)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 34 publications
0
8
0
2
Order By: Relevance
“…[ 28 ] It could also be attributed to the Ar bombardment during the welding cycles. [ 29 ] EDS test on the white colored regions have shown that they are composed of 36.83 at. % Cu, 21.96 at.…”
Section: Resultsmentioning
confidence: 99%
“…[ 28 ] It could also be attributed to the Ar bombardment during the welding cycles. [ 29 ] EDS test on the white colored regions have shown that they are composed of 36.83 at. % Cu, 21.96 at.…”
Section: Resultsmentioning
confidence: 99%
“…Dengan terbentuk lapisan permukaan aluminium nitrida (AlN) dan aluminium oksida (Al2O3) dapat mengubah sifat-sifat fisis dan kimia dari permukaannya. Kondisi tambahan unsur nitrogen (N) dan oksigen (O) sesuai dengan yang dilakukan pada proses nitridasi alumunium menggunakan nitridasi plasma radio frekuensi yang dilakukan oleh Hassan [11] yaitu pada waktu nitridasi 3 jam, 6 jam dan 9 jam. Dari analisis unsur menggunakan EDS pada nitridasi ini diperoleh unsur nitrogen (N) dan oksigen (O) masing-masing (wt %) adalah: 3,99% N dan 12,44% O untuk 3 jam, 4,31% O dan 18,61% N untuk 6 jam serta 8,78% N dan 4,01% O untuk 9 jam serta untuk nitridasi dengan >12 jam tidak ada unsur oksigen [11].…”
Section: Hasil Dan Pembahasan Analisis Sruktur Mikro Hasil Uji Sem-edsunclassified
“…Kondisi tambahan unsur nitrogen (N) dan oksigen (O) sesuai dengan yang dilakukan pada proses nitridasi alumunium menggunakan nitridasi plasma radio frekuensi yang dilakukan oleh Hassan [11] yaitu pada waktu nitridasi 3 jam, 6 jam dan 9 jam. Dari analisis unsur menggunakan EDS pada nitridasi ini diperoleh unsur nitrogen (N) dan oksigen (O) masing-masing (wt %) adalah: 3,99% N dan 12,44% O untuk 3 jam, 4,31% O dan 18,61% N untuk 6 jam serta 8,78% N dan 4,01% O untuk 9 jam serta untuk nitridasi dengan >12 jam tidak ada unsur oksigen [11]. Hal ini dimungkinkan karena terjadinya reaksi Al2O3 dengan N2 sehingga terbentuk AlN dan O2 dengan reakasi sebagai berikut [12]:…”
Section: Hasil Dan Pembahasan Analisis Sruktur Mikro Hasil Uji Sem-edsunclassified
“…Plasma nitriding has various parameters that can be used to do the treatment, such as substrate temperature, processing times, processing chamber pressure, gas composition, and input voltage [6], [7]. Plasma nitriding is more economical than other surface treatment methods and it needs shorter time of processing treatment [6].…”
Section: Introductionmentioning
confidence: 99%
“…Plasma nitriding has various parameters that can be used to do the treatment, such as substrate temperature, processing times, processing chamber pressure, gas composition, and input voltage [6], [7]. Plasma nitriding is more economical than other surface treatment methods and it needs shorter time of processing treatment [6]. Plasma nitriding itself is a surface hardening process of a metallic material involving the deposition of nitride layer and nitrogen diffusion into the metallic material in a vacuum chamber by making nitrogen into a plasma using high voltage between two electrodes (cathode and anode), so that the deposition and diffusion of nitrogen occurred on the surface of the material [8], [9].…”
Section: Introductionmentioning
confidence: 99%